Optimized Electronic Modification of S-Doped CuO Induced by Oxidative Reconstruction for Coupling Glycerol Electrooxidation with Hydrogen Evolution - Ruo-Yao Fan; Xue-Jun Zhai; Wei-Zhen Qiao; Yu-Sheng Zhang; Ning Yu; Na Xu; Qian-Xi Lv; Yong-Ming Chai; Bin Dong (Nano-Micro Letters, 2023)
Highlights S-doped CuO nanorod arrays (S-CuO/CF) constructed by sulfur leaching and oxidative remodeling strategy require only 1.23 and 1.33 V versus hydrogen evolution reaction (HER) to provide glycerol oxidation currents of 100 and 500 mA cm−2. S-CuO/CF shows satisfactory performance (at 100 mA cm−2, V cell = 1.37 V) assembled as the anode in asymmetric coupled electrolytic cell of glycerol oxidation reaction and HER. The study identifies the key factors involved in the GOR reaction pathway, which include the C–C bond breaking and lattice oxygen deintercalation steps.